REE Geochemistry of Euphrates River, Turkey - Leyla Kalender; Gamze Aytimur (Journal of Chemistry)
The study area is located on the Euphrates River at 38°41°32.48′′N–38°14′24.10′′N latitude and 39°56′4.59′′E–39°8°13.41′′E longitude. The Euphrates is the longest river in Western Asia. The lithological units observed from the bottom to the top are Permo-Triassic Keban Metamorphites, Late Cretaceous Kömürhan Ophiolites, Upper Cretaceous Elazığ Magmatic Complex, Middle Eocene Maden Complex and Kırkgeçit Formation, Upper Pliocene and Lower Eocene Seske Formation and Upper Miocene, Pliocene Karabakır and Çaybağı Formations, Palu Formation, and Holocene Euphrates River sediments. The geochemical studies show that 87Sr/86Sr and 143Nd/144Nd isotopic compositions in the Euphrates River bank sediments are 0.7053, 0.7048, and 0.7057 and 0.512654, 0.512836, and 0.512775, respectively. These values indicate mixing of both carbonate-rich shallow marine sediment and felsic-mafic rocks from Elazığ Magmatic Complex into the stream sediments. The positive εNd (0) values (0.35, 3.9, and 2.7) are higher downstream in the studied sediments due to weathering of the mafic volcanic rocks. The chondrite, NAS, and UCC normalized patterns show that the REE compositions of the Euphrates River sediments are higher than chondrite composition but close to NAS and UCC. The river sediments in the tectonic zone and the weathered granodioritic rocks of the Elazığ Magmatic complex affect upstream water compositions.